1992
DOI: 10.1007/bf03008643
|View full text |Cite
|
Sign up to set email alerts
|

Onset of vecuronium neuromuscular block is more rapid in patients undergoing Caesarean section

Abstract: This investigation was carried out in ten patients undergoing elective Caesarean section and the results were compared with those of a control group of ten nonpregnant females of the same age group. The study investigated the onset of vecuronium neuromuscular block and the conditions of tracheal intubation when ketamine (1.5 mg.kg-1)-vecuronium 100 micrograms.kg-1) sequence was used for rapid-sequence induction of anaesthesia. The ulnar nerve was stimulated supra-maximally at the wrist with train-of-four stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In contrast to mivacurium, the clinical duration of vecuronium-induced block is prolonged and the requirements are reduced in the pregnant and postpartum patient. 24,25 In conclusion, we have demonstrated that maintenance of mivacurium-induced neuromuscular block during elective Caesarean section could be achieved with the use of an on-demand SCR technique guided by the direct assessment of abdominal muscle tone. Compared with a continuous infusion given by the attending anaesthetist to maintain 95-100% at the hand muscles, the SCR technique was associated with reduced mivacurium requirement, a substantial degree of neuromuscular recovery at the end of surgery, a shorter time to adequate recovery, and a reduced need for neostigmine antagonism.…”
Section: Discussionmentioning
confidence: 79%
“…In contrast to mivacurium, the clinical duration of vecuronium-induced block is prolonged and the requirements are reduced in the pregnant and postpartum patient. 24,25 In conclusion, we have demonstrated that maintenance of mivacurium-induced neuromuscular block during elective Caesarean section could be achieved with the use of an on-demand SCR technique guided by the direct assessment of abdominal muscle tone. Compared with a continuous infusion given by the attending anaesthetist to maintain 95-100% at the hand muscles, the SCR technique was associated with reduced mivacurium requirement, a substantial degree of neuromuscular recovery at the end of surgery, a shorter time to adequate recovery, and a reduced need for neostigmine antagonism.…”
Section: Discussionmentioning
confidence: 79%
“…Prolonged neuromuscular blockade with succinylcholine is uncommon, however, as the increased volume of distribution offsets the impact of decreased drug hydrolysis [24]. Vecuronium at a standard dose of 0.2 mg/kg has been shown to have a faster onset time and longer duration of action in pregnancy [25]. The onset time of rocuronium at a dose of 0.6 mg/kg is unchanged but also demonstrates a longer duration of action compared with nonpregnant patients [26].…”
Section: Drugs In Pregnancy 41 Pharmacologymentioning
confidence: 98%
“…Ketamine has been shown to improve intubating conditions when used in association with rocuronium [11]. Ketamine can be safely used for the induction of general anesthesia in patients undergoing cesarean section with possible hypovolemia or with acute asthma [12,13]. The drug produces minimal respiratory depression and usually increases arterial blood pressure by 10 to 25 percent.…”
Section: General Anesthesiamentioning
confidence: 99%
“…Using ketamine for induction of general anesthesia in parturients who were undergoing cesarean section not only facilitates tracheal intubation at 50% NMB but, may allow the administration of 100% oxygen without anesthetic supplementation until delivery of the newborn [13]. However, because of the sympathomimetic effects of ketamine, it is contraindicated in hypertensive and preeclamptic parturients.…”
Section: General Anesthesiamentioning
confidence: 99%